2017
DOI: 10.2147/copd.s126607
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to high-cost hospital care for patients with COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of hospital admission, the fifth leading cause of death in North America, and is estimated to cost $49 billion annually in North America by 2020. The majority of COPD care costs are attributed to hospitalizations; yet, there are limited data to understand the drivers of high costs among hospitalized patients with COPD. In this study, we aimed to determine the patient and hospital-level factors associated with high-cost hospital care, in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
(26 reference statements)
2
26
0
Order By: Relevance
“…This condition is characterized by its chronicity and frequent acute exacerbations that contribute to a significant deterioration of the patients' health, affect the disease's progression and control, and result in a strong demand for health care resources, with the consequent socioeconomic impact, which accounts for 60%-70% of the costs of this disease [1][2][3]. An additional problem associated with this condition is that a significant number of patients admitted to the hospital for an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) will be readmitted in the following weeks or months, as demonstrated in many studies reporting readmission rates of 20%, 35%, and 60% at 30, 90, and 365 days, respectively [3][4][5][6][7][8][9][10]. The detection of factors that may allow us to predict these events has been the subject of multiple research studies carried out in recent years, as this would allow us to stratify the risks more accurately and apply interventions aimed at the most vulnerable groups of patients [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition is characterized by its chronicity and frequent acute exacerbations that contribute to a significant deterioration of the patients' health, affect the disease's progression and control, and result in a strong demand for health care resources, with the consequent socioeconomic impact, which accounts for 60%-70% of the costs of this disease [1][2][3]. An additional problem associated with this condition is that a significant number of patients admitted to the hospital for an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) will be readmitted in the following weeks or months, as demonstrated in many studies reporting readmission rates of 20%, 35%, and 60% at 30, 90, and 365 days, respectively [3][4][5][6][7][8][9][10]. The detection of factors that may allow us to predict these events has been the subject of multiple research studies carried out in recent years, as this would allow us to stratify the risks more accurately and apply interventions aimed at the most vulnerable groups of patients [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the available literature is very heterogeneous, the most frequently described predictive variables can be categorized as those related to the patient (previous admissions, severity of the condition, need for oxygen therapy or at-home ventilation, older age, low quality of life, comorbidities, low socioeconomic level, low therapeutic adherence, or active smoking) and those related to the health system (duration of previous hospital admissions, absence of a defined follow-up program, or poor health education) [3][4][5][6][7][8][9][10][11][12][13]. Although some studies have reported that the patients' deficient social situation are predictive factors for readmission and mortality, the analyses carried out to date have been very scarce and solely based on data regarding the patients' level of education, economic income, or the characteristics of the patients' home or caregivers and which have not been collected systematically [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Length of hospital stay (LOS) for AECOPD has a major impact on the costs of disease management [10]. Although common reasons impacting upon protracted hospital lengths of stay include social issues at home or bed blocking at postdischarge facilities [10], the early identification of patients with a higher risk of a prolonged LOS could help to target specific interventions.…”
Section: Patients With a High Risk Of Prolonged Staymentioning
confidence: 99%
“…Length of hospital stay (LOS) for AECOPD has a major impact on the costs of disease management [10]. Although common reasons impacting upon protracted hospital lengths of stay include social issues at home or bed blocking at postdischarge facilities [10], the early identification of patients with a higher risk of a prolonged LOS could help to target specific interventions. Some clinical variables [11] such as the presence of cor pulmonale (OR 2.19; 95% CI 1.27 to 3.78), the respiratory rate at admission (OR 1.09; 95% CI 1.03 to 1.14) or the hospitalization in the weekend (OR 4.17; 95% CI 2.42 to 7.18) increase the risk of prolonging hospital stay beyond three days [11].…”
Section: Patients With a High Risk Of Prolonged Staymentioning
confidence: 99%